Non-technological and non-economic innovations: Contributions to a theory of robust innovation - Steffen Roth (AVMpress Akademische Verlagsgemeinschaft, 2015)
Although the label innovation is applied to almost everything, with even the diffusion of innovations to society being called innovation, innovation research remains focused on bringing technology to the economic market. This dissonance provoked the central questions discussed at the 2nd International Conference on Indicators and Concepts of Innovation (ICICI). What are non-technological and non-economic innovations? What impact do these innovations have on the economy? Are there actually purely technological or economic innovations? Consisting of selected answers to these questions, this volume presents international approaches beyond the technology to market mainstream of innovation research as well as analyses of socially robust innovations that succeed in both economic and non-economic markets and are hence more sustainable and more profitable. The 2nd ICICI has been supported by the SCOPES program of the Swiss National Science Foundation.
Keywords: A14; Z13; 330; Social Innovation; Innovation; ICICI; Innovation